The influence of CSR and corporate governance on the risk of share prices in banking in Indonesia - Agnessa Britannia Paragina; Farah Margaretha Leon (The Management Journal of Binaniaga, 2020)
Abstract: This research was conducted to determine whether social responsibility and corporate governance actually have a significant effect on the risk of the company's stock price. The independent variable in this study is social responsibility and corporate governance, while the dependent variable is the risk of stock prices. There are four control variables in this study, namely company size, return on equity (ROE), earnings per share (EPS), and stock price volatility. This study collects data from 26 banking companies listed on the Indonesia Stock Exchange over a period of 5 years (2014-2018) and uses a multiple regression model for testing. The findings of this study indicate that social responsibility, company size, ROE, EPS, and stock price volatility have no significant effect on stock price risk. Meanwhile, corporate governance has a significant positive effect on stock price risk. The results of this research can be used to present a successful model for banking companies in Indonesia to concentrate more on social responsibility and corporate governance in mitigating their share price risk. All studies have used NCSKEW and DUVOL as measures of share price risk. In the novelty of this study, the Coefficient of Variation is used to measure the dependent variable so that the measurement can be distinguished from previous studies. Keywords: Banking Industry, Corporate Social Responsibility, Corporate Governance, Multiple Regression, Stock Price Risk